2016
DOI: 10.4142/jvs.2016.17.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Post-pandemic seroprevalence of human influenza viruses in domestic cats

Abstract: The continuous exposure of cats to diverse influenza viruses raises the concern of a potential role of cats in the epidemiology of these viruses. Our previous seroprevalence study of domestic cat sera collected during the 2009 H1N1 pandemic wave (September 2009–September 2010) revealed a high prevalence of pandemic H1N1, as well as seasonal H1N1 and H3N2 human flu virus infection (22.5%, 33.0%, and 43.5%, respectively). In this study, we extended the serosurvey of influenza viruses in cat sera collected post-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…We provide the first serological evidence of infection of cats with H3, H5, H7 and H9 subtypes in Europe. Such observations are in agreement with seroprevalence studies of cat sera conducted in Asia and the USA (41,50,51). Although significantly lower (p= 0.0069) seroprevalence of antibodies against avian IAVs could be detected in dogs compared to cats (Table 1), in some dog sera antibody responses against H5 and H7 were detected using different assays, including HI for H7.…”
Section: Downloaded Fromsupporting
confidence: 87%
“…We provide the first serological evidence of infection of cats with H3, H5, H7 and H9 subtypes in Europe. Such observations are in agreement with seroprevalence studies of cat sera conducted in Asia and the USA (41,50,51). Although significantly lower (p= 0.0069) seroprevalence of antibodies against avian IAVs could be detected in dogs compared to cats (Table 1), in some dog sera antibody responses against H5 and H7 were detected using different assays, including HI for H7.…”
Section: Downloaded Fromsupporting
confidence: 87%
“…Surveillance following the emergence of 2009 H1N1pdm showed a number of infections in cats (including fatalities) for that virus (Löhr et al 2010;Pingret et al 2010;Sponseller et al 2010;Campagnolo et al 2011;Fiorentini et al 2011;McCullers et al 2011;Su et al 2013b;Pigott et al 2014;Zhao et al 2014;Knight et al 2016;Tangwangvivat et al 2019), and experimental inoculations also confirmed susceptibility of cats to that strain (Bao et al 2010;van den Brand et al 2010). Cats are generally at low seroprevalence for other human influenza strains (Ali et al 2011;Zhang et al 2015b;Ibrahim et al 2016).…”
Section: Human Influenza Virus Spillover Into Dogs and Catsmentioning
confidence: 97%
“…For example, increased seroprevalence of pH1N1 virus in cats after the 2009 pandemic was detected by serosurveillance studies suggested sustained transmission of this virus in cat populations. 19 , 30 , 77 To date, few serosurveillance studies have been performed for SARS-CoV-2 in domestic dogs, cats, and mink, indicating a need for further serosurveillance studies in human-animal interfaces that represent a critical point for cross-species transmission. 45 , 46 , 48 , 76 …”
Section: Epidemiology and Serological Surveillance In Reverse Zoonosimentioning
confidence: 99%